The response of Tufted Ghost Crab, Ocypode cursor, populations to recreational activities in an urbanized coast with small-scale protected zones. Issue 1 (2nd January 2021) - Bal, Melisa; Çağrı Yapan, Batuhan; Özkan, Korhan
Abstract : Tufted Ghost Crabs ( Ocypode cursor ) experience local population declines and also range contractions at larger spatial scales due to increasing anthropogenic pressures on coastal ecosystems. Therefore, the environmental drivers of the decline in ghost crab populations and the efficiency of protection measures are needed to be better understood for more efficient coastal management. We surveyed Tufted Ghost Crab populations along a 3 km coastline in the Levant Basin of the Mediterranean, which hosts two protected with low and two public beaches with intense human recreational use. Abundance and distribution of the crabs were surveyed along 24 transect counts. The protected beaches hosted more burrows than corresponding nearby public beaches and the ghost crabs in the protected beaches inhabited a larger habitat band. Furthermore, Tufted Ghost Crab populations in the protected beaches consisted of more diverse age groups than that of public beaches, which lacked the smaller size crabs. Overall, our survey corroborated the role of Tufted Ghost Crabs as indicator species of coastal ecosystems and demonstrated the potential role of small protected zones within urbanized coastal regions as refugia for Tufted Ghost Crabs.